THE ILLNESS EXPERIENCE IN HYPERTENSION PATIENTS WITH LOW SOCIOECONOMIC STATUS - Hamzah, Imam Faisal; Subandi, Subandi (Jurnal Psikologi, 2020)
Hypertension is one type of disease that is usually experienced by adults, where arteries have excessive pressure, which is above 140 mm Hg for systolic and diastolic 90 mm Hg. Hypertension is not only a physical experience, but also needs to be understood as a psychological and social experience. Health is a social problem because it is related to how a person finances his health and access appropriate health facilities. The purpose of this study was to obtain psychosocial dynamics in the experience of hypertension in patients with low socioeconomic status. This study used a qualitative method with an Interpretative Phenomenological Analysis (IPA) approach through semi-structured interviews. Three participants involved were female, aged 30 to 45 years, and had more than one year suffered from hypertension. This study found six superordinate themes that focused on perceptions of causes, perceptions of hypertension, unpleasant feeling, social resources, improvement efforts, and health development.